EVALUATION OF STATUTORY PROVISIONS RELATING TO THE PROFESSION OF SWORN TRANSLATOR IN POLAND. AN ATTEMPT AT SUMMING-UP - KUBACKI, Artur Dariusz (Comparative Legilinguistics, 2019)
The paper focuses on an evaluation of statutory provisions relating to the profession of sworn translator in Poland. The Act on the Profession of Sworn Translator and its associated statutory instruments have been in force since 27 January 2005. After more than 13 years of operation of this legal framework, it is worth summing up whether the legal solutions put forward by the Polish legislature make it easier to practice the profession of sworn translator. The author discusses, inter alia, the recommendations of the Panel for Review and Assessment of Operation of the Act on the Profession of Sworn Translator, formed on 21 July 2015 by the Minister of Justice, and the legislative changes proposed by translation experts in order to improve the status and financial situation of sworn translators. Moreover, he suggests several solutions which – in his opinion based on many years' experience as a practising sworn translator and a certified translation theoretician – would greatly facilitate the work of sworn translators and would raise its quality.